On guarantees, vetoes and random dictators - Anna Bogomolnaia; Ron Holzman; Hervé Moulin (Theoretical Economics, 2023)
A mechanism guarantees a certain welfare level to its agents, if each of them can secure that level against unanimously adversarial others. How high can such a guarantee be, and what type of mechanism achieves it? In the n-person probabilistic voting/bargaining model with p deterministic outcomes a guarantee takes the form of a probability distribution over the ranks from 1 to p. If n≥p the uniform lottery is shown to be the only maximal (unimprovable) guarantee. If n<p, combining (variants of) the familiar random dictator and voting by veto mechanisms yields a large family of maximal guarantees: it is exhaustive if n=2 and almost so if p≤2n. Voting rules à la Condorcet or Borda, even in probabilistic form, are ruled out by our worst case viewpoint.
Keywords: D63; D71; 330; guarantees; random dictator; voting by veto; Worst case